Consumer perception toward genetically modified food in the Klang Valley, Malaysia - Bashir, Ibrahim Muse (2013)
Gene technology in Agriculture is rapidly increasing in the world, through which the latest modern biotechnology and best techniques is used to exclusively change the genes of one organism to another one, resulting in benefits to the world’s fastest growing population by ensuring sustainable food production. Genetically modified foods consist of food producing plants and animals which have experienced gene manipulation. The overall concept behind genetic modified food is the changing of the traits of genes in animals and plants in a way that results in greater production. From the ongoing GM development in terms of production has been progressive in the world especially in the developing countries. These developments came as a result of many advantages emphasised by several scientists and crop producers around the world in applying biotechnology techniques in the food industry. The benefits, though many, include the possibilities of finding a better solution to the existing and growing fear of world’s hunger problem by producing food that have high quality and longer shelf-life. However, the controversies in agricultural biotechnology scenario are mostly considered as a consumer related issue. The lack of reliable information on biotechnology may cause exaggeration from the public, especially when GM Food opposing parties raise their voice to aggravate certain emotional response from the public. It is understood in the past decade that lack of efforts and attention paid in scoping, caterogizing and most important explaining what is and not GM Food by the experts resulted more confusion among the public and tends to resist GM Food products consumption. As a result of these issues, this study aimed to determine Malaysian consumers’perception towards genetically modified foods. To achieve this objective, a survey was carried out in Klang Valley, Malaysia, on which one thousand two hundred and twenty seven respondents were interviewed by structured questionnaire to gather information on their perception, awareness and knowledge towards genetically modified foods. Behavioural perspective model is applied in this study. A seven point Likert scale from “Strongly Disagree” to “Strongly Agree”, were used to measure consumers perception. Descriptive statistics, chi-square, factor analysis and binary logistic regression were used to analyse the data obtained after collection. The analysis of the data shows that most of the respondents are aware of the existence of the GM food in Malaysia, though the majority of consumers hardly buy GM labelled foods or GM food products. The study indicates that the majority of the consumers were concerned with the GM food risks, heath-related effects resulting from GM food consumption and the long-term side effects from GM planting. In addition, the study highlights the existence of a relationship between consumers’ socio-demographic characteristics such as income, education level, gender, race, lifestyle and area with consumer awareness towards GM food, their concern towards risk and benefit from GM food consumption. Based on the factor analysis, six factors were identified that had influence on the consumers’ perception towards GM food. These factors included; food safety concern, consumer learning history and society impact, consumer awareness and belief of GM food, information about GM food, consumer utilitarian and consumer aversive.Moreover, the results from the binary logistic shows the presence of significance correlation between most of the consumers’ socio-demographic variables especially age, income and education level with the dependent variables which were consumers’awareness and perception towards GM foods. With respect to the increasing consumer awareness on the food safety and health consciousness towards genetically modified foods, it is then essential that marketing strategies should be developed to cope with the changing phenomenon by the respected government bodies or other respective organisations. However, understanding consumer awareness and understanding of the biotechnology foods or foods produced using biotech techniques is very vital to the food industry or food marketers. Furthermore, the market for GM foods is still a new concept to Malaysians, more effort should be carried out to disseminate the genetically modified food products concept and the consumption of biotech food to Malaysians in general. Therefore, food producers or marketers need to understand consumer behaviour and how Malaysian consumers purchasing behaviour is affected by their socio-demographic characteristics.